Malus toringoides (Rehd.) Hughes improves glucose and lipid metabolism and liver injury in high fructose‐induced mice. Issue 7 (25th March 2022) - Quan, Xianghua; Guo, Qie; Li, Xiangpeng; Liang, Yu; Cui, Mengna; Li, Jing; Huang, Shan; Wang, Jule; Li, Bin
Abstract: Malus toringoides (Rehd.) Hughes, as a traditional medicinal and edible plant used in Tibet, China, is used to treat hypertension, hyperlipidemia, and liver diseases. In recent decades, excessive fructose intake with diet has greatly increased the occurrence of a series of metabolic diseases including obesity, insulin resistance, hypertension, and hyperlipidemia. The present study was designed to investigate the effects of an ethanol extract of M. toringoides (EMT) on glucose and lipid metabolism and liver injury in high fructose‐induced mice. The C57BL/6J male mice were orally administrated with 30% fructose solution for 8 weeks, and EMT was given orally for another 8 weeks. The level of liver lipids related parameters, hepatic oxidative stress, and inflammatory mediators was detected by the kits. The improving effects of EMT on liver injury and lipid accumulation of mice were observed by hematoxylin and eosin staining and Oil Red O staining. In vitro, the hypolipidemic effect of EMT on palmitic acid‐induced HepG2 cells was detected by the kits and Oil Red O staining. Our results showed that EMT has the hypolipidemic effect in vivo and in vitro, and can improve liver injury caused by fructose intake though ameliorating oxidative stress and inflammatory responses. Thus, we suggested that EMT may be a candidate therapeutic agent to improve a series of metabolic diseases including obesity, insulin resistance, and hyperlipidemia. Practical applications: Our study was aimed to find a novel candidate drug for liver diseases using natural products. We assessed the protective effects of Malus toringoides (Rehd.) Hughes in the pathogenesis of glucose and lipid metabolism. In vivo, the plant significantly improved the disorder of blood lipid and blood glucose, and liver injury in mice induced by fructose, and in vitro, this plant significantly improved the lipid accumulation of HepG2 cells induced by palmitic acid. To sum up, our studies suggested that the plant may be beneficial in the prevention and management of diet‐induced abnormal glucose and lipid metabolism and liver diseases. Therefore, it will be a candidate therapeutic agent to improve liver diseases. Abstract : In vivo, the ethanol extract of M. toringoides (EMT) significantly improved the disorder of blood lipid and glucose, and liver injury in fructose‐induced mice. In vitro, EMT significantly improved the lipid accumulation of HepG2 cells induced by palmitic acid. Our studies suggested that the plant may be beneficial in the prevention and management of diet‐induced abnormal glucose and lipid metabolism and liver diseases.